2023
DOI: 10.3389/fpsyt.2023.1105987
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and cell senescence candidate genes screening, machine learning, diagnostic models, and drug prediction

Abstract: BackgroundSchizophrenia (SC) is one of the most common psychiatric diseases. Its potential pathogenic genes and effective treatment methods are still unclear. Cell senescence has been confirmed in mental diseases. A link exists between cellular senescence and immunity, and immune-related problems affect suicide rates in individuals suffering from schizophrenia. Therefore, the aims of this study were to identify candidate genes based on cell senescence that can affect the diagnosis and treatment of schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Multiple studies have demonstrated that neuronal cell death often transpires due to ferroptosis ( Ren et al, 2023 ; Wang D. et al, 2023 ). In our previous research, we have identified connections between psycho-neuro-degeneration and various factors, including programmed cell death (PCD), mitochondrial function, vesicular transport, and cuproptosis ( Feng and Shen, 2023 ; Feng et al, 2023 ; Shen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that neuronal cell death often transpires due to ferroptosis ( Ren et al, 2023 ; Wang D. et al, 2023 ). In our previous research, we have identified connections between psycho-neuro-degeneration and various factors, including programmed cell death (PCD), mitochondrial function, vesicular transport, and cuproptosis ( Feng and Shen, 2023 ; Feng et al, 2023 ; Shen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shortened telomeres in white blood cells serve as a key indicator of cell senescence. Feng et al.‘s study employs genetic tools to explore novel treatments for schizophrenia, highlighting the immunoglobulin gene myosin light chain kinase (MYLK) as a potential drug target for mental health therapeutic intervention ( 92 ).…”
Section: Research Studies In the Present Topicmentioning
confidence: 99%
“…are gut microbes also known for interfering with the dopaminergic signaling, further linking cellular senescence to insufficient DA [31,32]. This is significant since both treated and untreated SCZ patients were found to exhibit body-wide premature cellular/neuronal aging, linking this condition to abnormal intestinal permeability [33,34]. Indeed, SCZ was associated with increased microbial migration into the host systemic circulation [35][36][37].…”
Section: Premature Cellular Senescence In Schizophreniamentioning
confidence: 99%